Morbid obesity is adversely associated with perioperative outcomes in patients undergoing robot-assisted laparoscopic radical prostatectomy - Han, Hedong; Cao, Zhexu; Qin, Yingyi; Wei, Xin; Ruan, Yiming; Cao, Yang; He, Jia (Canadian Urological Association Journal, 2020)
Introduction: Robot-assisted laparoscopic radical prostatectomy (RALRP) may be more challenging in obese individuals. This study aimed to evaluate whether obesity had an adverse effect on perioperative outcomes following RALRP. Methods: Hospitalized patients who underwent RALRP from 2008– 2014 were identified using the National Inpatient Sample database. We grouped RALRP patients into non-obese, obesity class I–II, and obesity class III (morbid obesity). Rates of blood transfusion, intraoperative and postoperative complications, in-hospital mortality, prolonged length of stay, and total costs were compared among the three groups by univariate regression, multivariate regression, and propensity score weighting analysis. Results: Of 53 301 patients identified, 48 725 were non-obese, 3572 were diagnosed with obesity class I–II, and 1004 were diagnosed with morbid obesity. Compared to non-obesity (7.62%), overall postoperative complications were commonly observed in obesity class I–II (10.55%) and morbid obesity (17.11%). Multivariable analyses suggested that morbid obesity was associated with increased overall postoperative (odds ratio [OR] 2.00, 95% confidence interval [CI] 1.65–2.42), cardiac (OR 1.63, 95% CI 1.03–2.58), respiratory (OR 4.03, 95% CI 3.04–5.36), genitourinary (OR 1.77, 95% CI 1.08–2.90), miscellaneous medical (OR 1.94, 95% CI 1.58–2.39) complications, prolonged hospitalization (OR 1.86, 95% CI 1.57–2.21), and 12% higher total cost. Propensity score weighting analysis yielded similar results. Adequate covariate balance was achieved for all variables after weighting. Conclusions: Morbid obesity is adversely associated with perioperative outcomes in RALRP. Close management is required in patients undergoing RALRP with morbid obesity for potential worse prognosis.